Circulating Tumor Cell and Regulator T-Lymphocyte in Core Biopsy for Breast Cancer - Panigoro, Sonar Soni; Kartini, Diani; Wulandari, Dewi; Supono, Arif (The New Ropanasuri Journal of Surgery, 2020)
Introduction: Breast cancer is the most common malignancy found in Indonesia. Core biopsy is one of the modalities used in breast cancer diagnosis with sensitivity of 91-99% and specificity of 96-100%. The procedure causes damage to tumor tissue thus causing tumor cells to enter circulation (CTC) and therefore acute inflammation and infiltration of inflammatory cells. In the final phase of infiltration, the number of Tregs cells will increase, as well as secretion of TGFβ and IL-10, creation of immunosuppresion microenvironment, COX2 stimulation by TGFβ then conversion of CD4+ T cells into FoxP3+ (Tregs), therefore the number of Tregs cells will increase. SOX-4 is activated by TGFβ, and then EMT proccess occurs, tumor cells enter circulation and CTC number will increase. Considering the side effect of core biopsy which is entrance of tumor cells to circulation causing the procedure to be in debate/contradicting opinions. Based on this premise, this study aims to investigate whether there is a change and relationship in Tregs count and CTC count before and after core biopsy procedure. Methods: This study includes 32 blood sample from patients with Stage III and IV breast cancer who went to surgical oncology outpatient clinic in Dr. Cipto Mangunkusumo National Central General Hospital (RSCM) and Gatot Subroto Army Hospital (RSPAD) before and 2 weeks after core biopsy during August to December 2016. Blood is sent to Clinical Pathology Laboratory of RSCM-FKUI to be measured its Tregs count (CD4, CD25, FoxP3 biomarker) and CTC count (CK19 biomarker) using flow cytometry. Statistical analysis was performed using Wilcoxon to determine the difference in CTC/Tregs count before and after core biopsy. Spearman correlation test was performed to determine the relationship between Tregs count and CTC count. Results: Results showed decrease in number of CTC after core biopsy with P value of 0.569 (p > 0.05). There was a decline in Tregs count after core biopsy with p value of 0.049. Small rho value (r=0.165, r=0.235, r=0.046) and p value greater than 0.05 signifies that there is no association between Tregs count to CTC count before or after procedure. Conclusion: Core biopsy do not cause increase in CTC or Tregs, however it cannot be concluded that the procedure is safe, despite the significant finding is only in the decline of Tregs count but not for CTC count. There is no association between Tregs count to CTC count before or after core biopsy.